Institutional Labyrinth : Designing a Way Out for Improving Urban Transport Services--Lessons from Current Practice - Kumar, Ajay (World Bank, Washington, DC, 2014)
Severe congestion, poor air quality, increases in road accidents, and explosive growth in energy consumption are manifestations of rapid motorization in cities around the globe, especially in the developing world. The tendency in most developing cities has been to deal with these problems in a piecemeal fashion, largely through supply side interventions, such as widening roads, constructing flyovers, or building high-cost mass transit systems. It is becoming increasingly recognized that effective solutions lie in comprehensive and holistic approaches that integrate what would normally be patchwork efforts and, in addition, combine supply side efforts with demand side measures. In general, this means that multiple, well-integrated actions need to be taken. Integrated and comprehensive thinking and implementation is required across multiple subsystems and disciplines, such as land use planning, environmental quality, energy efficiency, and services for the poor and physically disadvantaged. The ability to undertake comprehensive planning and execution that is integrated functionally, spatially, sectorally, and hierarchically is too often constrained because of the highly fragmented governance of urban transport in most cities. The functions that need to be performed can be classified as strategic, tactical, and operational. Strategic functions include policy formulation and long-range planning; tactical functions involve regulation and detailed planning; and operational functions concern the construction of facilities and ensuring the availability of services. National governments can play a pivotal role through their ability to provide financing to lead agencies at lower levels of government and take advantage of economies of scale by coordinating and undertaking activities of interest to multiple cities, such as capacity building and research.